ANALISIS PERANGKAT PEMBELAJARAN TEMATIK DI KELAS IV SEKOLAH DASAR NEGERI 14 PONTIANAK UTARA - Tanti Purwanti; Siti Halidjah; Tahmid Sabri (Universitas Tanjungpura, 2020)
Abstract The aim of this research is to describe the analysis of thematic learning tools in grade IV of 14 North Pontianak Elementary Schools. The research this method used is descriptive with a qualitative approach. The data source of this research is a teacher who teaches as a homeroom teacher for class IV of 14 North Pontianak Elementary School. The results showed that the learning tools compiled by the teacher were in the form of lesson plans, teaching materials and evaluation, some were appropriate and some were not in accordance with Permendikbud number 22 of 2016. The teaching materials chosen must be in accordance with the basic competencies contained in the lesson plans. Learning evaluation must be in accordance with the four Core Competencies (KI), namely (KI-1), (KI-2), (KI-3) and KI-4) which are expected to be achieved by students in each semester.